1996
DOI: 10.1111/j.1523-536x.1996.tb00458.x
|View full text |Cite
|
Sign up to set email alerts
|

Women's Satisfaction with Prenatal Care Settings: A Focus Group Study

Abstract: Knowledge of how the characteristics of prenatal care affect women's satisfaction can help increase use of care and ultimately improve perinatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
51
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 21 publications
1
51
0
Order By: Relevance
“…This coincides with regular prenatal care visits, where the Prenatal EHC could be completed in the waiting room prior to the visit, and integrates topics recommended for prenatal psychological screening. Our findings are consistent with other studies demonstrating that patients’ value when their health care providers focus on psychosocial issues (Bertakis, Roter, & Putnam, 1991; Handler, Raube, Kelly, & Giachello, 1996; Korenbrot, Wong, & Stewart, 2005). The inclusion of discussion about psychosocial issues can be viewed as an opening up of the communication in the visit that has been previously demonstrated to increase patient satisfaction with prenatal care (Handler, Rosenberg, Raube, & Lyons, 1998).…”
Section: Discussionsupporting
confidence: 92%
“…This coincides with regular prenatal care visits, where the Prenatal EHC could be completed in the waiting room prior to the visit, and integrates topics recommended for prenatal psychological screening. Our findings are consistent with other studies demonstrating that patients’ value when their health care providers focus on psychosocial issues (Bertakis, Roter, & Putnam, 1991; Handler, Raube, Kelly, & Giachello, 1996; Korenbrot, Wong, & Stewart, 2005). The inclusion of discussion about psychosocial issues can be viewed as an opening up of the communication in the visit that has been previously demonstrated to increase patient satisfaction with prenatal care (Handler, Rosenberg, Raube, & Lyons, 1998).…”
Section: Discussionsupporting
confidence: 92%
“…A review on general health services delivery in China reported that many patients complained about unclear information about services they received and a few of them or their relatives had open conflict with health providers [27]. Studies in both industrialised and developing countries have found that good patient-provider interaction was associated with increased women's satisfaction [28,29], which was considered as one of the major factors influencing the use of prenatal care and the effect of care [30]. The lack of clear and effective communication suggested in this study may not only undermine the provider-user relationship, but also potentially affect health seeking behaviour if patients are unwilling to seek care due to lack of trust.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative methods allow women to reveal their feelings in greater depth than survey research methods [34]. In fact, most studies aimed at exploring women's views about quality of reproductive health care resort to interviews and focus groups [12]. However, results obtained with these techniques cannot be extrapolated and have low external validity.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we analyzed the differences between the perspectives of women in the intervention and control clinics, focusing only on those specific aspects that changed as a result of the introduction of the new ANC model (number and spacing of visits, information provided, etc.) Our study did not explore women's satisfaction with any other aspects of ANC such as technical quality, physical environment, access and continuity of the provider [37,38] that were not modified with the intervention, or the differences in users' satisfaction associated with ANC received in different types of facilities (i.e. private or public.)…”
Section: Discussionmentioning
confidence: 99%